2003
DOI: 10.1128/jcm.41.10.4879-4882.2003
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Respiratory Syncytial Virus in Infants Hospitalized for Acute Lower Respiratory Infection in Chile (1989 to 2000)

Abstract: Hospitalized infants (4,618) were studied for lower respiratory infections from 1989 through 2000 by routine immunofluorescence assay and viral isolation. The hospitalization rate for respiratory syncytial virus (RSV) averaged 2% per year. The fatality rate was 0.1%. Monthly RSV detection varied from 14 to 88%, and epidemics lasted 3.5 to 6 months. From 1994 high-early versus low-late epidemic patterns alternately were observed, the first influenced by a group B strain.Acute respiratory infections are a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 23 publications
(31 reference statements)
3
41
0
8
Order By: Relevance
“…In Chile and Argentina, most studies on HRSV have been based on analyses of epidemiological and clinical aspects of HRSV infections and viral antigenic group typing [Videla et al, 1998;Lagos et al, 1999;Carballal et al, 2000;Imaz et al, 2000;Avendañ o et al, 2003] The main objective of the present study was to examine the antigenic diversity within groups of HRSV strains recovered during consecutive outbreaks in Buenos Aires (Argentina) and Santiago (Chile) from 1995 to 2002. As second objective, we proposed to compare the antigenic patterns of Argentinean and Chilean HRSV strains circulating during the same period (1999)(2000)(2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chile and Argentina, most studies on HRSV have been based on analyses of epidemiological and clinical aspects of HRSV infections and viral antigenic group typing [Videla et al, 1998;Lagos et al, 1999;Carballal et al, 2000;Imaz et al, 2000;Avendañ o et al, 2003] The main objective of the present study was to examine the antigenic diversity within groups of HRSV strains recovered during consecutive outbreaks in Buenos Aires (Argentina) and Santiago (Chile) from 1995 to 2002. As second objective, we proposed to compare the antigenic patterns of Argentinean and Chilean HRSV strains circulating during the same period (1999)(2000)(2001).…”
Section: Introductionmentioning
confidence: 99%
“…This study was undertaken as part of a multicenter project that involved different laboratories from South America [Avendañ o et al, 2003;Frabasile et al, 2003;Moura et al, 2004]. The use of an ELISA with MAbs directed against the G glycoprotein of HRSV was chosen as suitable method to evaluate strain diversity, since in our countries is very expensive to perform nucleotide sequencing and genotyping for a large number of strains.…”
Section: Introductionmentioning
confidence: 99%
“…8,14 In South America, especially in the southern part of the continent (i.e., Chile and Argentina), some studies have shown a clear seasonality, with a peak around the fall and winter months (May to August). 5,7 However, in equatorial regions that lack dramatic seasonal temperature variations (i.e., Fortaleza, Brazil), RSV infection may have a peak in the rainy season (January to August). 15 In this study, we were not able to define a clear-cut RSV seasonality.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated to cause approximately 33 million new episodes of acute lower respiratory infections in children annually and about 53,000-199,000 deaths annually in young children; 96% of episodes and 99% of deaths occur in developing countries. 1,2 In Latin America, there are several studies on the epidemiology of RSV infections in children [2][3][4][5] ; however, there are limited data on the disease burden of these infections in high-risk groups, such as pre-term infants. 6,7 Prevention of RSV disease relies on infection control and hygiene measures as well as provision of immunoprophylaxis in select infants.…”
Section: Introductionmentioning
confidence: 99%
“…Varias publicaciones nacionales concuerdan en demostrar el impacto de la influenza como causa de hospitalización en lactantes sanos 13,[15][16][17][18] . La mayoría de las hospitalizaciones pediátricas ocurren en niños bajo 2 años de edad y alrededor de 60% en lactantes bajo 12 meses, afectando en su gran mayoría (60-75%) a niños sanos, los que no son incluidos en los grupos de riesgo "tradicionales" con indicación de vacuna [15][16][17][18] . Más de 50% presenta complicaciones como sobreinfección bacteriana pulmonar, otitis media aguda (OMA) o insuficiencia respiratoria 15 .…”
Section: Epidemiologíaunclassified